Standardization of protocol for in vitro propagation of banana (Musa sapientum) (Journal of the Bangladesh Agricultural University, 2018)
An experiment was conducted at the Plant Biotechnology Laboratory, Department of Horticulture, Patuakhali Science and Technology University during the period from August 2016 to April 2017 to standardize the protocol for in vitro propagation of banana. The experiment was laid out in completely randomized design with four replications. Three to four months aged field grown rhizome attached shoots were used as explants and cultured on MS medium with different concentrations and combinations of BAP (6-benzylamino purine), BAP + KIN (Kinetin) + NAA (Naphthalene Acetic Acid) and IBA (Indole-3- Butyric Acid) + IAA (Indole-3- Acetic Acid) to observe their efficacy on single shoot initiation, shoot multiplication and root formation respectively. Minimum number of days required for shoot initiation (9.07) with highest shoot initiation percentage (91.14) and the longest shoot (2.23 cm) was found in MS medium supplemented with 5.0 mg/L BAP. On the other hand, highest shoot multiplication percentage (80.99) with maximum number of shoots per explant (4.47), the highest length of shoots (4.17 cm) and maximum number of leaves (4.04)was observed in MS medium supplemented with 4.0 mg/L BAP + 2.0 mg/L KIN + 2.0 mg/L NAA. In case of root regeneration, the best results on days required for root initiation (9.00), the highest root initiation percentage (85.05), maximum number of roots per plantlet (5.83) and the highest length of roots (4.17 cm) was obtained in MS medium supplemented with1.5 mg/L IBA + 0.5 mg/L IAA. After 5-7 days of hardening in room temperature, established plantlets were ready for plantingJ. Bangladesh Agril. Univ. 16(1): 27-30, April 2018